Validity and reliability of the Critical-Care Pain Observation Tool (CPOT) for critically ill pediatric patients - Haruhiko Hoshino; Mitsuki Ikeda; Yujiro Matsuishi; Yuki Enomoto; Nobutake Shimojo; Misaki Kotani; Shunsuke Kobayashi; Takahiro Kido; Satomi Hayashi; Yoko Furuya; Yoshiaki Inoue (PLoS ONE, 2025)
Introduction In some regions, critically ill pediatric and adult patients are cared for in the same intensive care unit, complicating pain assessment due to mixed age groups. To address this, it is essential to use pain scales that are applicable to a wide age range. The Critical-Care Pain Observation Tool (CPOT) was developed to assess pain in both intubated and non-intubated adult patients. However, its applicability in pediatric patients has not been confirmed. The purpose of this study was to evaluate CPOT for critically ill pediatric patients. Methods We conducted a prospective observational study in an eight-bed open PICU from January 2022 to March 2023. Three research nurses independently assessed pain using CPOT, the Face, Legs, Activity, Cry, Consolability (FLACC) scale, and an Observational Visual Analog Scale (VAS obs). Criterion-related and construct validity were examined using Spearman’s rank correlation coefficients between CPOT, VAS obs, and FLACC. Diagnostic performance was evaluated via ROC analysis using a FLACC score ≥ 4 as the reference. CPOT scores with and without medical interventions were compared using the Mann–Whitney U test, and inter-rater reliability was assessed with Cohen’s weighted κ. Results Ninety-one patients were observed 165 times. CPOT strongly correlated with VAS obs (Spearman’s ρ =  0.87, p <  0.01) and FLACC (Spearman’s ρ =  0.84, p <  0.01). At a CPOT cut-off score of 3, sensitivity was 100% and specificity was 96.7%. CPOT effectively reflected pain levels during medical interventions (p <  0.01), and inter-rater reliability was high (weighted κ =  0.89, 95% CI: 0.799–0.941). Conclusions This study suggests that CPOT may be a useful tool for pain assessment in pediatric patients.